PM.53 CRADLE: Community Blood Pressure Monitoring in Rural Africa: Detection of underLying Pre-Eclampsia. (26th April 2013) - Hezelgrave, NL; Irvine, L; Radford, S; Seed, P; Mazanhi, P; Edmunds, S; Basira, D; Chikwezveru, K; Shennan, AH
Abstract : Introduction: In developing countries pre-eclampsia is under-detected partly due to inadequate training in accurate blood pressure (BP) measurements and insufficient equipment. CRADLE is an international study to evaluate whether the introduction of novel, low-cost, automated BP devices into rural clinics in Tanzania, Zimbabwe and Zambia increases referrals for suspected pre-eclampsia to a central referral hospital. This will be reflected in an increased mean BP in pregnant women presenting centrally. Methods: Prospective longitudinal pre- and post-intervention study. BP measurements were taken from consecutive women ≥20 weeks gestation who accessed care at a referral site (N = 694). Intervention: 20 BP devices were distributed to 20 rural antenatal clinics in each country. Post-intervention data was collected the following year (N = 547). Results: After adjustment for confounders, there was a significant increase in our primary outcome, post-intervention mean diastolic BP, for all women, implying an increased proportion of referred hypertensive women (2.39 mmHg, p < 0.001, 95% CI 0.97–3.8) and a reduction in proportion of women (median gestation 35 weeks) who had never previously had a BP in pregnancy, (25.1% to 16.9%, OR 0.58, p = 0.001, CI 0.42–0.79). In Zimbabwe there was an additional significant increase in the proportion of women who had sustained hypertension (12.8% to 21.3%, OR 1.09, p = 0.03, CI 1.06–3.43). Conclusion: Equipping low-skilled community health providers with a novel BP device is feasible and widely accepted, and increased community referrals for suspected pre-eclampsia. A cluster RCT to evaluate the effect of these monitors equipped with traffic light early warning systems, on maternal and fetal outcomes is planned.